(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The country Elam, one of the neighboring powers of Mesopotamia, and one of the areas of tension often, also had a significant Dorssayas in that experienced Mesopotamia of events, at least as important as the commercial and economic role, a role of RPR that fluctuate between war and peace over the years, and will deliver search more light on the side of the activity of the kings of the Assyrians a hundred and fifty years ago, it was characterized as a military richest in the history of Mesopotamia, in order to provide focused information on the relationship between Assyria and Elam, during the study period.